Impact of baseline characteristics on outcomes of carotid artery stenting in acute ischemic stroke patients - Yu CS; Lin CM; Liu CK; Lu HHS (Dove Medical Press, 2016)
Cheng-Sheng Yu,1,* Chih-Ming Lin,2,3,* Chi-Kuang Liu,4 Henry Horng-Shing Lu1 1Institute of Statistics and Big Data Research Center, National Chiao Tung University, Hsinchu, 2Stroke Centre and Department of Neurology, Chunghua Christian Hospital, Chunghua, 3Graduate Institute of Biological Science and Technology, National Chiao Tung University, Hsinchu, 4Department of Medical Imaging, Chunghua Christian Hospital, Chunghua, Taiwan, Republic of China *These authors contributed equally to this work Abstract: Carotid artery stenting is an effective treatment for ischemic stroke patients with moderate-to-severe carotid artery stenosis. However, the midterm outcome for patients undergoing this procedure varies considerably with baseline characteristics. To determine the impact of baseline characteristics on outcomes following carotid artery stenting, data from 107 eligible patients with a first episode of ischemic stroke were collected by retrospective chart review. A modified Rankin Scale (mRS) was used to divide patients into two baseline groups, mRS ≤2 and mRS >2. A three-step decision-tree statistical analysis was conducted. After weighting the decision-tree parameters, the following impact hierarchy was obtained: admission low-density lipoprotein, gouty arthritis, chronic kidney disease, ipsilateral common carotid artery resistance index, contralateral ophthalmic artery resistance index, sex, and dyslipidemia. The finite-state machine model demonstrated that, in patients with baseline mRS ≤2, 46% had an improved mRS score at follow-up, whereas 54% had a stable mRS score. In patients with baseline mRS >2, a stable mRS score was observed in 75%, improved score in 23%, and a poorer score in 2%. Admission low-density lipoprotein was the strongest predictive factor influencing poststenting outcome. In addition, our study provides further evidence that carotid artery stenting can be of benefit in first-time ischemic stroke patients with baseline mRS scores >2. Keywords: carotid artery stenting, modified Rankin Scale, ischemic stroke, finite-state machine, resistance index